360 degree white light holography display on surface of transparency conical cup - Srinuanjan, K.; Kamoldilok, S. (My University, 2021)
This paper presents the method and experimental results of the construction and reconstruction of three dimensions conical holography. He-Ne laser is used as the construction light source. Then the construction light is shone on top of a transparency conical cup, where a plain holographic film is wrapped around and attached to its surface. The object is located at the bottom of the cup. In this manner, the cup acts as a captured screen. After exposure, the film is developed and fixed by a chemical solution. The three-dimensional holography is recorded in the film. For reconstruction, we used red LED and flashlight as a reconstruction light source. The film is wrapped around and attached to the surface of the cup again. When the reconstruction light shines on the cup, the three-dimensional holography appears in the center of the cup. The cup is rotated in step, each step is 45 degrees, and the image is recorded by the digital camera. Experimental results show that the 360 degrees three-dimensional holographic image is successfully reconstructed. In conclusion, we could apply the method to create a three-dimensional holographic for displaying in all directions.
Keywords: 360 degrees holography; Conical holography; White holography